The art and science of technical analysis : market structure, price action, and trading strategies - Grimes, Adam, 1973- (Hoboken, N. J. : John Wiley & Sons, Inc., 2012)
'A breakthrough trading book that provides powerful insights on profitable technical patterns and strategiesThe Art and Science of Technical Analysis is a groundbreaking work that bridges the gaps between the academic view of markets, technical analysis, and profitable trading. The book explores why randomness prevails in markets most, but not all, of the time and how technical analysis can be used to capture statistically validated patterns in certain types of market conditions. The belief of the book is that buying and selling pressure causes patterns in prices, but that these technical patterns are only effective in the presence of true buying/selling imbalance.The Art and Science of Technical Analysis is supported by extensive statistical analysis of the markets, which will debunk some tools and patterns such as Fibonacci analysis, and endorse other tools and trade setups. In addition, this reliable resource discusses trader psychology and trader learning curves based on the author's extensive experience as a trader and trainer of traders. Offers serious traders a way to think about market problems, understand their own performance, and help find a more productive path forward Includes extensive research to validate specific money-making patterns and strategies Written by an experienced market practitioner who has trained and worked with many top traders Filled with in-depth insights and practical advice, The Art and Science of Technical Analysis will give you a realistic sense of how markets behave, when and how technical analysis works, and what it really takes to trade successfully'--
Includes bibliographical references (p. 443-445) and index.
Keywords: Investment analysis